Correction: Lemen, R.A.; Landrigan, P.J. Sailors and the Risk of Asbestos-Related Cancer. Int. J. Environ. Res. Public Health 2021, 18, 8417 - Richard A. Lemen (MDPI AG, 2021)
There was an error in the original article [...]